Federation Pharmacological Safety in Pregnancy: Modern Knowledge, Practice and Pharmacoepidemiological Approaches to the Studying and Recognizing of Drugs with Teratogenic Risk - Konstantin A. Lutsevich; Olga V. Reshetko (Union of pediatricians of Russia, 2019)
One of the key issues in obstetric practice remains the lack or incompleteness of information on the teratogenicity of most drugs used by pregnant women. Uncertainty regarding teratogenic risks significantly affect the quality of information on drugs; nevertheless, counseling patients allows arriving at a more balanced solution regarding their risk in pregnancy. Determination of the most commonly taken drugs (prescription or OTC) in the first trimester of gestation and increase of knowledge on their embryofetal risks optimizes pharmacotherapy during pregnancy. Characteristics and epidemiological analysis of possible factors, including drugs, associated with the occurrence of congenital anomalies, are crucial for the development of prevention activities that have an impact on the incidence of defects.